2021
DOI: 10.13005/bpj/2127
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Observational Study on Prescribing Pattern of Antifungal Drugs in the 400 Out-Patient Department of Dermatology in a Tertiary Care Hospital

Abstract: Introduction: Fungal infections have been a serious disease over a few decades. Superficial fungal infections not only cause life-threatening illnesses but slowly reduce the Quality of life of patients. Objective: To study the prescribing pattern of antifungal drugs, distribution of fungal disease, and cost variability between different antifungal drugs prescribed. Materials and methods: Prospective observational study was carried out at Justice K.S. Hegde Charitable Hospital from August 2018 to April 2019. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…33 Itraconazole and terbinafine are the recommended antifungal agents to be used as first-line treatment options for systemic therapy. 8 Commonly prescribed oral AFs were itraconazole capsules (41%) followed by terbinafine tablets (11%) which is in accordance with a similar study by Chandrajeet et al, 31 and Naaz et al 34 The topical AFs were ketoconazole cream (19%) followed by luliconazole (11%) which is similar to Chandrajeet et al's 31 findings of 19.65% and Naaz et al 34 reported luliconazole (34%) followed by ketoconazole (30%). The prescriptions were analysed for co-prescribed antihistamines and found that CPM tablets (68%) were highly prescribed followed by hydroxyzine Hcl (25%).…”
Section: Treatment Pattern and Prescribing Practicesupporting
confidence: 82%
See 1 more Smart Citation
“…33 Itraconazole and terbinafine are the recommended antifungal agents to be used as first-line treatment options for systemic therapy. 8 Commonly prescribed oral AFs were itraconazole capsules (41%) followed by terbinafine tablets (11%) which is in accordance with a similar study by Chandrajeet et al, 31 and Naaz et al 34 The topical AFs were ketoconazole cream (19%) followed by luliconazole (11%) which is similar to Chandrajeet et al's 31 findings of 19.65% and Naaz et al 34 reported luliconazole (34%) followed by ketoconazole (30%). The prescriptions were analysed for co-prescribed antihistamines and found that CPM tablets (68%) were highly prescribed followed by hydroxyzine Hcl (25%).…”
Section: Treatment Pattern and Prescribing Practicesupporting
confidence: 82%
“…These findings were slightly contradictory to findings by Chandrajeet et al 31 who reported levocetirizine (13.99%) followed by hydroxyzine Hcl (12.42%). A study by Naaz et al 34 showed that levocetirizine (37.3%), hydroxyzine (10%) followed by CPM (4.8%). The high usage of CPM might be attributed to its free availability in the hospital‐free pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…18 And among the topical anti-fungals, luliconazole cream (175.6%) showed the maximum cost variability in our study, this was also contradictory to the study done by author Naaz et al where ketoconazole cream showed the maximum cost of variation. 19…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, appropriate antifungal drugs are very important to treat the condition and prevent the complications of fungal infections. 5 Vast varieties of systemic and topical antifungal drugs are available in the market. Amphotericin B, fluconazole, itraconazole, capsofungin, griseofulvin and terbinafine are commonly used systemic antifungal drugs in India.…”
Section: Introductionmentioning
confidence: 99%
“…7 Among these antifungal drugs are most commonly prescribed in dermatological conditions as combination therapy of systemic and topical antifungal agents. 5 Antifungal drugs are available in various dosage forms like tablets, capsules, injections, creams, lotions, powder, shampoo, ear drops, etc. 1 Fixed-Dose Combinations of antifungal drugs with antimicrobials, corticosteroids, and local anesthetic drugs are also prescribed in some conditions.…”
Section: Introductionmentioning
confidence: 99%